Metabolite Profiles Predict Acute Kidney Injury and Mortality in Patients Undergoing Transcatheter Aortic Valve Replacement. Issue 3 (March 2016) - Elmariah, Sammy; Farrell, Laurie A.; Daher, Maureen; Shi, Xu; Keyes, Michelle J.; Cain, Carolyn H.; Pomerantsev, Eugene; Vlahakes, Gus J.; Inglessis, Ignacio; Passeri, Jonathan J.; Palacios, Igor F.; Fox, Caroline S.; et al.
Abstract : Background: Acute kidney injury (AKI) occurs commonly after transcatheter aortic valve replacement (TAVR) and is associated with markedly increased postoperative mortality. We previously identified plasma metabolites predictive of incident chronic kidney disease, but whether metabolite profiles can identify those at risk of AKI is unknown. Methods and Results: We performed liquid chromatography–mass spectrometry–based metabolite profiling on plasma from patients undergoing TAVR and subjects from the community‐based Framingham Heart Study (N=2164). AKI was defined by using the Valve Academic Research Consortium‐2 criteria. Of 44 patients (mean age 82±9 years, 52% female) undergoing TAVR, 22 (50%) had chronic kidney disease and 9 (20%) developed AKI. Of 85 metabolites profiled, we detected markedly concordant cross‐sectional metabolic changes associated with chronic kidney disease in the hospital‐based TAVR and Framingham Heart Study cohorts. Baseline levels of 5‐adenosylhomocysteine predicted AKI after TAVR, despite adjustment for baseline glomerular filtration rate (odds ratio per 1‐SD increase 5.97, 95% CI 1.62–22.0; P =0.007). Of the patients who had AKI, 6 (66.7%) subsequently died, compared with 3 (8.6%) deaths among those patients who did not develop AKI ( P =0.0008) over a median follow‐up of 7.8 months. 5‐adenosylhomocysteine was predictive of all‐cause mortality after TAVR (hazard ratio per 1‐SD increase 2.96, 95% CI 1.33–6.58; P =0.008), independent of baseline glomerular filtration rate. Conclusions: In an elderly population with severe aortic stenosis undergoing TAVR, metabolite profiling improves the prediction of AKI. Given the multifactorial nature of AKI after TAVR, metabolite profiles may identify those patients with reduced renal reserve.